Life histories stories of homeless people, social exclusion situations and transforming encounters - Alvarez, Aparecida Magali de Souza; Alvarenga, Augusta Thereza de; Della Rina, Silvia Cristiane de S. A. (Saúde e Sociedade, 2009)
This work presents, based on life histories Stories, characteristics of a "transforming encounter" that took place between two homeless people and oneA teacher. and that was It was a positive "point of support" in their lives. "Transforming encounter" is an interaction between human beings that enables the transformation of the people involved, in the sense that their potentialities are awoken, they recover their direction of life, and their resilience is promoted. Resilience is the human capacity to deal with life's adversities, overcome them;so, and become stronger and even transformed. The longitudinal study that was conducted involved the obtention of life histories stories through open interviews, photographs, registers in a Field Diary and drawings made by the observation subjects. In the data interpretation, concepts from certain theories were used, p.from the following areas (e.g.: Psychology, Geography, Sociology, Law, Education Sciences, Complexity and Systemic Theory), in a dialog among different disciplines. The analysis of the phenomenon analysis - in which living on the street emerged as an excluding existential situation - revealed a new configuration in the homeless' psyches, which were undergoing a transformation movement. The observed phenomenon - awhich was complex one - showed the difficulty that the studied homeless individuals have into maintaining themselves in the resilient process without the effective support of the CCivil Society's and of the State's support, through public policies targeted at this kind of population. The conclusion is that the results of this work are important as a contribution to the amplification of education processes amplification, not only of professionals who work with the homeless people, but also of members of society in general, guided by solidarity and by the will to search - for citizenship - conditions for all.